From Servant Leadership to Cadre Retention: Cadre Education as an Institutional Mechanism (Political HRM) in Political Parties - Saleh, Taufik; Dina, Nur; Mulyani, Sri (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
contributes to cadre retention by positioning cadre education programs as the primary institutional mechanism. The study examines whether cadre retention is influenced directly and indirectly by servant leadership, with cadre education and development programs conceptualized as Political Human Resource Management (Political HRM) and positioned as a key mediating variable. The study employs a quantitative approach using a structured questionnaire survey administered to members of a cadre-based political party organization. From a total population of 2,073 registered cadres recorded in the organizational database, all were internally ensured to receive the research questionnaire, and 551 respondents voluntarily completed it (voluntary random sample). The data were subsequently analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with a hierarchical component model (HCM) two-stage approach to model multidimensional constructs. The findings indicate that servant leadership does not have a significant direct effect on cadre retention; however, it exerts a very strong influence on the quality of cadre education and development programs, which in turn have a positive and significant effect on cadre retention. These results confirm an indirect-only mediation (full mediation) pattern. The model explains a substantial proportion of variance in cadre education programs (53.2%) and cadre retention (50.7%) and demonstrates strong predictive relevance, underscoring that retention in cadre-based organizations is predominantly system-driven.This study offers a conceptual and empirical model that extends the understanding of how leadership operates in value-based political organizations by positioning institutional mechanisms as the primary pathway through which leadership influences cadre sustainability. The study contributes to the leadership, organizational retention, and HRM systems literature by introducing Political HRM as an institutional architecture that translates leadership values into long-term cadre development systems.